Betty A. Reardon: A Pioneer in Education for Peace and Human Rights - Reardon, Betty A (Springer, 2016)
Betty A. Reardon is a world-renowned leader in the fields of peace education and human rights; her pioneering work has laid the foundation for a new cross-disciplinary integration of peace education and international human rights from a gender-conscious, global perspective. This collection of reflective inquiry and ongoing research gathers essential works on peace education and human rights (1967-2014) and provides access to Reardon’s key works. These texts have been foundational to the field of peace education during the past five decades of her practical experience. The unique conceptualization of a holistic framework for organizing content and the practical and specific descriptions of pedagogies for the practice of critical peace education in schools and universities, have made them essential resources for peace educators around the world; several have already become standard texts for basic courses in the field. The book also includes an overview of Reardon’s career and a bibliography of her publications.